2016
DOI: 10.1080/10503307.2016.1246765
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pre-dropout and temporary rupture sessions in psychotherapy

Abstract: A striking implication is that the frequency of positive and negative psychotherapist behaviors, ruptures, and session content is more likely to decrease in the pre-dropout sessions than in the temporary rupture sessions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Our findings show how important it is for therapists to be attentive to the nonverbal processes occurring during the sessions, in addition to the explicit words that are being said by patients. Ruptures that are not addressed and do not undergo a process of repair and resolution might have negative effects on therapy, such as deterioration and premature dropout (Eubanks et al, 2018; Gülüm et al, 2018). In addition to the content of the session, nonverbal synchrony may serve as an additional layer helping identify and assess confrontation ruptures using an automatic approach that does not require the investment of high cost, time, or effort.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show how important it is for therapists to be attentive to the nonverbal processes occurring during the sessions, in addition to the explicit words that are being said by patients. Ruptures that are not addressed and do not undergo a process of repair and resolution might have negative effects on therapy, such as deterioration and premature dropout (Eubanks et al, 2018; Gülüm et al, 2018). In addition to the content of the session, nonverbal synchrony may serve as an additional layer helping identify and assess confrontation ruptures using an automatic approach that does not require the investment of high cost, time, or effort.…”
Section: Discussionmentioning
confidence: 99%
“…For the long term, as more studies will be accumulated that show nonverbal synchrony as a marker of the alliance, it will be possible to develop an in-session automatic feedback system that will give the therapist, as well as the patient, feedback on the nonverbal markers of the alliance (Delgadillo et al, 2017). This is especially important for withdrawal ruptures in the alliance, which studies have shown that patients and therapists are often not aware of or decide not to report (Eubanks et al, 2019), and at the same time might have negative effects on the treatment, such as premature dropout (Eubanks et al, 2018; Gülüm et al, 2018). A live in-session feedback feature could alert the therapist when such ruptures go unnoticed.…”
Section: Discussionmentioning
confidence: 99%
“…The idea of offering CBM-I prior to existing therapy protocols may be even more attractive for populations with increased levels of hostility. That is, patients with increased hostility levels are at an increased risk to engage in hostile interactions with therapists (von der Lippe et al, 2008), which negatively impacts working alliance (Gülüm et al, 2018). One study showed that working alliance positively mediated the relationship between low levels of hostility and treatment outcome in dialectical behavior therapy for borderline personality disorder (Hirsh et al, 2012).…”
mentioning
confidence: 99%